Online training system Metta Pracharak Hospital (Wat Rai Khing) Basic Ophthalmic Nursing Course - Patan, Vacharatit (Thammasat University Hospital Journal Online, 2023)
Background: Metta Pracharak Hospital (Wat Rai Khing), Department of Medical Services, is a tertiary care institution and afflicted institution for teaching residents in ophthalmology. It provides is medical teaching for professional nurses both inside and outside the organization. The professional nurses must give lectures to other professional nurses who attend the training, in order to gain knowledge and give care advice of patients and their relatives with ophthalmology on a continuous basis every year. Because of the COVID-19 pandemic in 2020 - 2022, the onsite training program could not be done. Therefore, an online training system Metta Pracharak Hospital (Wat Rai Khing) for Basic Ophthalmic Nursing Course was developed. Objectives: To develop a hybrid online training format combined with case study for learning activities and cooperative learning on basic ophthalmology courses. To increase analytical thinking skills in eye diseases for professional nurses in 13 health service areas nationwide. Material and methods: 1) Explore the demand for training content. 2) System analysis and design for testing. 3) Preparation of teaching and learning content. Preparation of certification were based on the Nursing Council of Thailand standard. It is an educational model by implementing the model to Provide online and on-site training. Knowledge before and after training were measured. Result: Online training system was effective in transferring knowledge in ophthalmology, which had an impact on the development of professional nurses' knowledge in by this technology, without on-site training courses in other provinces. It is budget savings and can be learned from anywhere at anytime. Measured training results was done before and after training. In 2022, this course was approved by the Nursing Council of Thailand, receiving 11.5 consecutive education score units. Conclusion: Online training system https://www.mettatraining.com/ is an informative technology innovation for effective academic knowledge transfer. The students can learn anytime and anywhere. Standard measurement of learning outcome will bring knowledge in screening, preventing and caring of the public.